Outcomes of Surgical Resection in the Management of Colorectal Pancreatic Metastases - Farid, Shahid G; Morley, Lara; Roberts, Keith J; Morris-Stiff, Gareth; Smith, Andrew M (JOP. Journal of the Pancreas, 2014)
Context Colorectal pancreatic metastases (CRPM) are uncommon, thus the role of surgical resection is unclear. We present our experience of management outcomes of patients with CRPM in a regional pancreatic unit. Methods Electronic records of all patients with colorectal cancer (n = 8,228) held by the cancer network were searched for evidence of CRPM. Retrospective analysis of each case was undertaken in relation to diagnosis, management and outcome of CRPM. Results Four cases of CRPM underwent resection (operative group). The interval between diagnosis of colorectal carcinoma and CRPM was 1, 6, 7 and 7 years. CRPM were identified on routine CT surveillance in asymptomatic patients. An additional 5 patients were managed palliatively (non-operative group). In the surgical cohort, median survival was 4 years. One patient remains disease free 4 years 3 months post-surgery. Of 3 patients with recurrent disease, 1 is alive with progressive disease 3 years 11 months post-operatively and 2 passed away at 18 months and 5 years 1 month respectively. Median survival in the palliative group from diagnosis of CRPM was 11 months. Conclusions In selected patients with CRPM surgical resection does confer survival benefit. CRPM arise late in the disease course, with extra-pancreatic metastases frequently diagnosed in the interim. Surgeons outside of pancreatic units should refer cases to their local pancreatic multi-disciplinary team meeting for consideration of resection. Image: St James’s University Hospital (Leeds, UK) logo.